Innovation instruction in the academic library: A new focus. Issue 2 (3rd April 2019) - Caruso, Beth
Abstract: Innovation spaces are quickly being implemented into academic libraries. But while these spaces generate outward excitement from those who wish to use them, they, and the projects introduced within them, can also intimidate students that feel forced to use such spaces. Therefore, it is vital that we not only acknowledge these intimidation factors in developing instruction, but also that we lead students away from any uncertainties surrounding emerging technology use. The approaches described will provide librarian innovation instructors with methods for introducing intimidated, atypical users to nontraditional and emerging technologies and will outline concrete activities that librarians can use to move students toward manageable takeaways.